Implementasi Kebijakan Pemanfaatan Sistem Informasi Manajemen Daerah (SIMDA) dalam Pelaporan Keuangan Pemerintah Daerah Kabupaten Biak Numfor: Studi pada Badan Pengelola Keuangan dan Aset Daerah/BPKAD Kabupaten Biak Numfor - Saipan, Saipan; Iriawan, Hermanu; Dahlan, Dahlan (VISA: Journal of Vision and Ideas, 2024)
The purpose of researchers using this type of descriptive research with a qualitative approach, so that researchers can collect information that is in accordance with reality and can answer all formulations that focus on Implementation and Supporting and Inhibiting Factors for Regional Management Information System (SIMDA) Utilization Policy in Financial Reporting of the Biak Numfor Regency Government. The primary data obtained comes from SIMDA Structural Officers and Operators at the Regional Equipment Organization (OPD) of the Regional Financial and Asset Management Agency (BPKAD) of Biak Numfor Regency and Secondary comes from financial statement data for the last 4 years. Data collection techniques are carried out by means of interviews, observations and documentation studies using data analysis, data presentation, data condensation, data presentation so as to draw a conclusion. The results showed that the implementation of the SIMDA Finance policy in BPKAD Biak Num Regency went well. However, there are still inhibiting factors such as limited competent officers/operators, limited budget/funds, and human error in inputting data.